Applied international economics - Sawyer, W. Charles; Sprinkle, Richard L. (New York : Routledge, 2020)
"Applied International Economics, 5th edition, offers a modern and accessible treatment of international economics, shifting the emphasis from pure theory to the application of theory by using the standard tools of economic analysis. This new and streamlined edition makes the real-world application of international economics even more clear than previous editions, and focuses on the basics that students will need in order to analyze information on the world economy throughout their future careers. The new edition has been refocused, revised, and thoroughly updated. Key features include: Expanded coverage of China's role in the world economy. New material on the how changes in trade flows can be decomposed into the extensive and intensive margins of trade. New material on the use of Section 301 of U.S. trade law and the U.S. - China trade dispute. Updated coverage of Brexit. A new focus on the sole use of the Mundell-Fleming model to analyze balance of payments issues. Improved linkages between the concepts of purchasing power parity and the real exchange rate. Written in a thorough and engaging style, the book covers topics at a level appropriate for students specializing in business or international relations, as well as economics students. Along with a wealth of case studies and real-life examples, the book offers extensive pedagogical tools that include include a companion website, end of chapter summaries, and explanations of key concepts and terms. For instructors, power point presentations and an extensive test bank are available"--
Revised edition of the authors' Applied international economics, 2015.
OCLC-licensed vendor bibliographic record.
Keywords: International economic relations; International finance; BUSINESS & ECONOMICS / International / Economics; BUSINESS & ECONOMICS / Economics / Macroeconomics